Potential scales of structural transformation of the Russian electric power system based on low-carbon distributed generation (Advances in Systems Science and Applications, 2019)
This article considers conditions and scenarios of transformation of the traditional structure of generating capacity in the Russian electric power system in the next 10-15 years considering the mass decommissioning of operating thermal power plants (TPPs) and active development of low-carbon distributed generation (DG) technologies. For this purpose, the ultimate development potential of Russia's key distributed cogeneration technology was assessed, taking into account the forecast of capacity balance situation in the national electric power system. In addition to it, the possible scales of the involvement of renewable power (RES) plants, as well as the potential impact of consumer’s demand response (DR) programs to replace large-scale generating facilities are considered.